Flagellin phase‐dependent swimming on epithelial cell surfaces contributes to productive Salmonella gut colonisation. (18th April 2017) - Horstmann, Julia A.; Zschieschang, Erik; Truschel, Theresa; de Diego, Juana; Lunelli, Michele; Rohde, Manfred; May, Tobias; Strowig, Till; Stradal, Theresia; Kolbe, Michael; Erhardt, Marc
Abstract: The flagellum is a sophisticated nanomachine and an important virulence factor of many pathogenic bacteria. Flagellar motility enables directed movements towards host cells in a chemotactic process, and near‐surface swimming on cell surfaces is crucial for selection of permissive entry sites. The long external flagellar filament is made of tens of thousands subunits of a single protein, flagellin, and many Salmonella serovars alternate expression of antigenically distinct flagellin proteins, FliC and FljB. However, the role of the different flagellin variants during gut colonisation and host cell invasion remains elusive. Here, we demonstrate that flagella made of different flagellin variants display structural differences and affect Salmonella 's swimming behaviour on host cell surfaces. We observed a distinct advantage of bacteria expressing FliC‐flagella to identify target sites on host cell surfaces and to invade epithelial cells. FliC‐expressing bacteria outcompeted FljB‐expressing bacteria for intestinal tissue colonisation in the gastroenteritis and typhoid murine infection models. Intracellular survival and responses of the host immune system were not altered. We conclude that structural properties of flagella modulate the swimming behaviour on host cell surfaces, which facilitates the search for invasion sites and might constitute a general mechanism for productive host cell invasion of flagellated bacteria.